2021
DOI: 10.2340/16501977-2786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality-based neck-specific sensorimotor training in patients with chronic neck pain: A randomized controlled pilot trial

Abstract: Objective To evaluate the effects of neck-specific sensorimotor training using a virtual reality device compared with 2 standard rehabilitation programmes: with, and without general sensorimotor training, in patients with non-traumatic chronic neck pain. Design Pilot randomized control study. Patients and methods A total of 51 participants were randomly assigned to 1 of 3 groups: 1: control group; 2: sensorimotor group; 3: virtual reality gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 37 publications
3
79
0
Order By: Relevance
“…The majority of providers surveyed believe that VR helps their clients/patients progress in treatment compared to similar therapy without VR. These subjective findings corroborate previous studies that have shown the effectiveness of VR in treatment of phobias [4,11,12,[26][27][28], anxiety [5,6,10,13,20,29], PTSD [2,7,14], addictions [8,30,31], and pain management [2,3,15,16,18,32].…”
Section: Key Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of providers surveyed believe that VR helps their clients/patients progress in treatment compared to similar therapy without VR. These subjective findings corroborate previous studies that have shown the effectiveness of VR in treatment of phobias [4,11,12,[26][27][28], anxiety [5,6,10,13,20,29], PTSD [2,7,14], addictions [8,30,31], and pain management [2,3,15,16,18,32].…”
Section: Key Findingssupporting
confidence: 90%
“…Virtual reality (VR) is an innovative technology that allows the user to vividly experience scenarios via immersive, multi-sensory information, typically delivered via headset including visual and auditory cues. Clinical applications of this technology include the treatment of specific phobias, trauma, eating disorders, and also management of acute and of chronic pain [1,2]. Recent years have seen VR applications developed and integrated into many realms of psychiatry and behavioral medicine, particularly for the treatment of anxiety disorders [3][4][5][6], post-traumatic stress disorder (PTSD) [7], and pain management [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The participants reported that the VR intervention motivated them to exercise in many ways; it provided feedback, the levels encouraged them to reach a higher level, and it was important to perform the exercises correctly. The only negative effect noted was that the device was experienced as heavy, which was also observed in the study by Nusser et al ( 35 ).…”
Section: Discussionsupporting
confidence: 76%
“…The results showed increased function regarding mobility and speed in neck movements, and improved balance and increased patient satisfaction compared with kinematic training without VR ( 19 ). In a recently published pilot-study patients with non-traumatic chronic neck pain practiced sensorimotor training with a VR device in combination with a standard rehabilitation programme ( 35 ). The results were compared with those for patients who did not receive training with a VR device.…”
Section: Discussionmentioning
confidence: 99%
“…Coordination exercises, aiming to restore the active neck movements and retrain the fine movement control of the cervical spine, are reported to reduce pain and alter motor control strategy between deep and superficial cervical muscles (Rudolfsson et al, 2014). With the development of virtual reality (VR) techniques, the VR-based kinematic training on patients with neck pain shows improvements in range of motion, accuracy, velocity, smoothness, fine motor control and coordination of the cervical spine (Nusser et al, 2021). It is believed that the VR-based kinematic training could motivate the visual systems, vestibular systems and sensorimotor control system simultaneously in patients with neck pain (Sarig Bahat et al, 2015).…”
Section: Interventions Sensorimotor Control System Trainingmentioning
confidence: 99%